Mean platelet volume in acute rheumatic fever. (August 2013) - Sert, Ahmet; Aypar, Ebru; Odabas, Dursun
<x xml:space="preserve">Abstract</x> Acute rheumatic fever (ARF) is still an endemic disease, especially among school-aged children in developing countries. Mean platelet volume (MPV), which is commonly used as a measure of platelet size, indicates the rate of platelet production and platelet activation. We aimed to investigate MPV in children with ARF. The study population consisted of 40 children with ARF (32 patients with carditis and 8 patients without carditis) and 40 healthy control subjects. White blood cell (WBC) and platelet counts were significantly higher and MPV values were significantly lower in patients with ARF during the acute stage when compared to controls. Erythrocyte sedimentation rate (ESR) and C-reactive protein values significantly decreased in patients with ARF after the treatment when compared to baseline, whereas MPV values increased. MPV values were negatively correlated with ESR and WBC, and platelet counts. In conclusion, during the acute stage of ARF, MPV values were lower when compared to controls.